Effect of Operating Conditions on Pollutants Concentration Emitted from a Spark Ignition Engine Fueled with Gasoline Bioethanol Blends - Shahad, Haroun A. K.; Wabdan, Saad K. (Journal of Renewable Energy, 2015)
This study is an experimental investigation of the effect of bioethanol gasoline blending on exhaust emissions in terms of carbon dioxide CO2, carbon monoxide CO, unburnt hydrocarbons UHC, and nitric oxide NOx of a spark ignition engine. Tests are conducted at controlled throttle and variable speed condition over the range of 1200 to 2000 rpm with intervals 400 rpm. Different compression ratios are tested for each speed, namely (7,8,10, and 11). Pure gasoline and bioethanol gasoline blends are used. The bioethanol used is produced from Iraqi date crop (Zehdi). Blending is done on energy replacement bases. Ethanol energy ratio (EER) used is 5%, 10%, and 15%. At each of the three designated engine speeds, the torque is set as 0, 3, 7, 10, and 14 N·m. It is found that ethanol blending reduces CO and UHC concentration in the exhaust gases by about 45% and 40.15%, respectively, and increases NOx and CO2 concentrations in the exhaust gases by about 16.18% and 7.5%, respectively. It is found also that load and speed increase causes an increase in CO2 and NOx concentrations and reduces CO and UHC concentrations. It is also found that increasing the compression ratio causes the emissions of CO2 and NOx to decrease and those of CO and UHC to increase.